2017
DOI: 10.1180/minmag.2016.080.152
|View full text |Cite
|
Sign up to set email alerts
|

First crystal-structure determination of natural lansfordite, MgCO3·5H2O

Abstract: This study presents the first crystal-structure determination of natural MgCO3·5H2O, mineral lansfordite, in comparison with previous structural works performed on synthetic analogues. A new prototype single-crystal X-ray diffractometer allowed us to measure an extremely small crystal (i.e. 0.020 mm × 0.010 mm × 0.005 mm) and refine anisotropically all non-hydrogen atoms in the structure and provide a robust hydrogen-bond arrangement. Our new data confirm that natural lansfordite can be stable for several mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…MgCO 3 Á5H 2 O (mineral name: lansfordite), is known. Its crystal structure (monoclinic space group P2 1 /m) was determined by Liu et al (1990) from a synthetic sample and by Nestola et al (2017) from a mineral. Several possibilities are described to synthesize lansfordite (Ming & Franklin, 1985;Liu et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MgCO 3 Á5H 2 O (mineral name: lansfordite), is known. Its crystal structure (monoclinic space group P2 1 /m) was determined by Liu et al (1990) from a synthetic sample and by Nestola et al (2017) from a mineral. Several possibilities are described to synthesize lansfordite (Ming & Franklin, 1985;Liu et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, there are contradictory statements about the temperature and the rate of conversion of the pentahydrate to the trihydrate. Some research groups have recorded a transition temperature between 283.15 and 288.15 K (Takahashi & Hokoku, 1927;Gloss, 1937;Yanaťeva & Rassonskaya, 1961;Hill et al, 1982;Langmuir, 1965;Ming & Franklin, 1985), while others observed the stability of synthesized and natural samples of lansfordite at room temperature over a period of a few months (Liu et al, 1990;Nestola et al, 2017). Neutral magnesium carbonates with a water content greater than five units per formula are not known up to now.…”
Section: Introductionmentioning
confidence: 99%